Direct numerical simulation of H2/air combustion with composition stratification in a constant volume enclosure relevant to HCCI engines. (17th August 2016) - Zhang, F.; Liu, H.F.; Yu, R.; Yao, M.; Bai, X.S.
Abstract: Two-dimensional direct numerical simulation (2-D DNS) is used to investigate the effect of turbulence intensity and composition stratification on H2 /air mixture auto-ignition in a constant volume enclosure relevant to homogeneous charge compression ignition (HCCI) engines. Different turbulence levels, composition fluctuations, EGR (Exhaust Gas Recirculation) ratios, initial pressure, domain lengths and energy spectra are simulated with detailed analysis in ten 2-D DNS cases. The results show that the ignition delay time tends to be prolonged and the heat release rate increased under higher turbulence intensity. Turbulence can affect the reaction zone, e.g., through wrinkling of reaction front and enhancement of mixing and heat transfer. Higher composition stratification can smoothen the overall heat release rate and shorten the ignition delay time. Budgets terms and Probability Density Function (PDF) of density weighted displacement speed show that in HCCI engines flame propagation can co-exist with volumetric auto-ignition. As expected, lower pressure leads to thicker flame thickness and longer ignition delay time. Increasing EGR ratio has a negative influence on the formation of OH reaction, resulting in a longer ignition delay time. Two energy spectra with respect to low and high Reynolds number are compared to show a discrepancy on ignition delay time due to different kinetic energy dissipation rates. Highlights: Higher turbulence result in a longer ignition delay time and a stronger heat release rate. Turbulence can affect the reaction zone, e.g., through wrinkling of reaction front and enhancement of mixing and heat transfer. Composition stratification can shorten ignition delay time and smoothen heat release rate. It is found that ignition wave and flame propagation wave co-exist. Low and high Reynolds number energy spectra are used to initialize 2-D DNS turbulence field.